Fuel cell separator and method for manufacturing fuel cell separator

The fuel cell separator with a three-layer structure of a metal substrate, conductive oxide film, and discrete precious metal particles addresses the challenge of maintaining low contact resistance in harsh environments, achieving cost-effectiveness and durability.

JP7662504B2Active Publication Date: 2025-04-15TMEIC CORP (100 00) +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021203496
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2025-04-15
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

Conventional fuel cell separators struggle to maintain low contact resistance with gas diffusion layers over time, especially in harsh environments, due to corrosion issues and high processing costs associated with applying noble metals uniformly.

Method used

A fuel cell separator with a three-layer structure comprising a metal substrate, an electrically conductive oxide film, and a group of precious metal particles, where at least a portion of the precious metal particles are provided discretely on the conductive oxide film, reducing the amount of precious metals needed and maintaining low contact resistance.

Benefits of technology

The proposed fuel cell separator effectively stabilizes low contact resistance between the precious metal particles and the conductive oxide film, even in severe environments, while minimizing the use of precious metals, thus reducing costs and maintaining performance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662504000001
    Figure 0007662504000001
  • Figure 0007662504000002
    Figure 0007662504000002
  • Figure 0007662504000003
    Figure 0007662504000003
Patent Text Reader

Abstract

To obtain a fuel cell separator with which it is possible to stably lower the contact resistance with an object which is to be contacted.SOLUTION: A pair of ATO films 21A are provided on the surface and reverse side of a metal substrate 20. One noble metal particle group 22G is provided on the top surface of the upper ATO film 21A, out of the pair of ATO films 21A, and an other noble metal particle group 22G is provided on the underside of the lower ATO film 21A. The pair of noble metal particle groups 22G include a plurality of noble metal particles 22, respectively, and each of the plurality of noble metal particles is composed from gold or platinum. Each of the plurality of noble metal particles 22 comes in the form of particulate, and at least some of the plurality of noble metal particles 22 are provided separately from each other. A fuel cell separator 2 is constituted including the metal substrate 20, the pair of ATO films 21A, and the pair of noble metal particle groups 22G.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a fuel cell separator that contacts a power generation section of a fuel cell, and a method for manufacturing the same. [Background technology]

[0002] A fuel cell of a polymer electrolyte fuel cell is made up of a membrane electrode assembly (MEA), which is made by bonding a solid polymer electrolyte membrane to an anode electrode and a cathode electrode to form an integrated body, sandwiched between separators that act as a flow path for hydrogen gas and other gases. Several of these cells are then stacked on top of each other to form a stack.

[0003] Fig. 12 is an explanatory diagram showing an exploded view of the cell structure of a fuel cell 60. An XYZ orthogonal coordinate system is depicted in Fig. 12. The fuel cell 60 shown in the figure is one unit cell, and the fuel cell 60 includes an MEA 5 and fuel cell separators 15 and 16 provided on either side of the MEA 5 as main components.

[0004] The MEA 5, which serves as the power generation section, includes as its main components a polymer electrolyte membrane 10, an anode catalyst layer 11, a cathode catalyst layer 12, a gas diffusion layer 13, and a gas diffusion layer 14. The anode catalyst layer 11, which serves as a cathode electrode, is provided on one main surface (the main surface in the -X direction) of the polymer electrolyte membrane 10, and the cathode catalyst layer 12, which serves as an anode electrode, is provided on the other main surface (the main surface in the +X direction) of the polymer electrolyte membrane 10.

[0005] When the fuel cell 60 is completed, the polymer electrolyte membrane 10 and the anode catalyst layer 11, and the polymer electrolyte membrane 10 and the cathode catalyst layer 12 are in close contact with each other, and the electrolyte membrane-catalyst layer intervals B1 and B2 shown in FIG. 12 do not exist.

[0006] Furthermore, a gas diffusion layer 13 is provided on one main surface of the negative electrode catalyst layer 11, and a gas diffusion layer 14 is provided on the other main surface of the positive electrode catalyst layer 12. The gas diffusion layer is also called a "GDL (Gas Diffusion Layer)."

[0007] Then, a fuel cell separator 15 is provided on one main surface of the gas diffusion layer 13. In this case, the fuel cell separator 15 is provided in such a manner that the surface of a protruding portion 15t (a portion protruding in the +X direction) contacts one main surface of the gas diffusion layer 13. Similarly, a fuel cell separator 16 is provided on the other main surface of the gas diffusion layer 14. In this case, the fuel cell separator 16 is provided in such a manner that the surface of a protruding portion 16t (a portion protruding in the -X direction) contacts the other main surface of the fuel cell separator 16.

[0008] The diffusion layer-separator gap B3 indicates the gap between the protruding portion 15t of the fuel cell separator 15 and the gas diffusion layer 13. The diffusion layer-separator gap B4 indicates the gap between the protruding portion 16t of the fuel cell separator 16 and the gas diffusion layer 14. Therefore, when the fuel cell 60 is completed, the diffusion layer-separator gaps B3 and B4 do not exist.

[0009] Meanwhile, even at the completed stage of the fuel cell 60, a separator flow path SP15 exists between the recess 15v of the fuel cell separator 15 and the gas diffusion layer 13, and a separator flow path SP16 exists between the recess 16v of the fuel cell separator 16 and the gas diffusion layer 14. The separator flow paths SP15 and SP16 serve as flow paths for hydrogen gas, heated acid solution, etc.

[0010] In the fuel cell 60 having such a structure, the pair of gas diffusion layers 13 and 14 provided on both sides within the MEA 5 are layers for providing a fuel gas or an oxidant gas, respectively, and for collecting electricity generated by the electrochemical reaction.

[0011] Therefore, in order to stabilize the power generation efficiency of the fuel cell 60, it is required to keep the electrical contact resistance low between the gas diffusion layer 13 and the fuel cell separator 15 (its convex portion 15t), and between the gas diffusion layer 14 and the fuel cell separator 16 (its convex portion 16t), which are in contact with each other, and further to maintain the low contact resistance even after the power generation process by the fuel cell 60 has been completed (first requirement).

[0012] Furthermore, the separator pairs 15 and 16 are exposed to an environment in which a voltage is applied in a heated acid solution during power generation in the fuel cell 60. For this reason, the separator pairs 15 and 16 are required to have high corrosion resistance against acids (second requirement).

[0013] In order to meet these first and second requirements, various improvements have been made to fuel cell separators in the past. For convenience of explanation, in the following description, "fuel cell separator" may be abbreviated to "separator" and "gas diffusion layer" may be abbreviated to "GDL."

[0014] An example of a conventional fuel cell separator that meets the first and second requirements described above is the fuel cell separator disclosed in Patent Document 1. This fuel cell separator has an antimony-doped tin oxide film (ATO film) formed on the surface of the separator for the purposes of ensuring the corrosion resistance of the separator and achieving low contact resistance with the GDL.

[0015] Furthermore, Patent Documents 2 to 6 are prior art documents that aim to reduce contact resistance by forming a precious metal on the separator surface.

[0016] Patent Document 2 proposes a method of forming a film of an alloy of a precious metal such as Au (gold) or Pt (platinum) with a non-precious metal such as Nb (niobium), Ta (tantalum), Zr (zirconium) or Hf (hafnium) on the surface of a separator substrate using a sputtering method or the like.

[0017] The technology disclosed in Patent Document 3 forms a precious metal film on the surface of a separator substrate (thin metal plate). The precious metal film is provided so that the average thickness is 10 nm or less, and the protrusions are 15 nm or more thick.

[0018] Patent Document 4 proposes a technique in which an aluminum substrate for a separator is plated with Ni (nickel) and then plated with Au.

[0019] Patent Document 5 proposes a technique for forming a film of dot-shaped Au particles on the protruding portions of a metal separator (metal substrate) by, for example, an inkjet method so that the area ratio of the protruding portions is 12% or more.

[0020] Patent Document 6 discloses a separator structure that includes a titanium oxide layer on a metal substrate made of titanium, and further includes a conductive coating made of conductive particles (size 1 to 100 nm) on the titanium oxide layer. [Prior art documents] [Patent documents]

[0021] [Patent Document 1] JP 2019-192437 A [Patent Document 2] JP 2010-182593 A [Patent Document 3] JP 2011-29008 A [Patent Document 4] JP 2013-105629 A [Patent Document 5] JP 2014-139884 A [Patent Document 6] JP 2012-190816 A Summary of the Invention [Problem to be solved by the invention]

[0022] However, the conventional fuel cell separators described above are insufficient in terms of satisfying the first and second requirements described above, as will be explained below.

[0023] The single layer of ATO contained in the conventional separator disclosed in Patent Document 1 was not sufficient to obtain the first requirement of low contact resistance. That is, it was difficult to reduce the contact resistance with the GDL in the conventional separator in which the surface was covered with a single layer of tin oxide film.

[0024] When realizing the separator disclosed in Patent Document 5, if a precious metal is applied to the entire surface of the separator substrate, the processing costs will be high.

[0025] On the other hand, when the precious metal is not formed on the entire surface of the base material, for example, a partially precious metal formed structure in which the precious metal is scattered on the surface of the substrate may be considered.

[0026] 13 is an explanatory diagram showing the problems with the conventional separator disclosed in Patent Document 5. A fuel cell separator 82 shown in Fig. 13(a) employs a precious metal partial formation structure, in which precious metal particles 25 are formed only on a portion of the surface of a metal substrate 20.

[0027] The fuel cell separator 82 partially formed with precious metal shown in Fig. 1(a) can be set to have a relatively low initial contact resistance immediately after the device is completed. However, the fuel cell separator 82 is exposed to a harsh environment during power generation in the fuel cell. In this environment, there is a high possibility that metals other than the precious metal will come into contact with a corrosive liquid, which will increase the contact resistance.

[0028] This is because, as shown in Fig. 13(b), an oxide layer 28 is formed on the surface of the metal substrate 20 where no precious metal is formed. Over a long period of time, the oxide layer 28 reaches the interface between the metal substrate 20 and the precious metal particles 25, and ultimately, as shown in Fig. 13(c), the metal substrate 20 and the precious metal particles 25 are separated by the oxide layer 28. In this way, if the degree of corrosion during the use of the fuel cell separator 82 is relatively large, the precious metal particles 25 may fall off from the fuel cell separator 82.

[0029] 13(c), the contact resistance of the fuel cell separator 82 becomes high after the oxide layer 28 is formed on almost the entire surface of the metal substrate 20. In this way, the conventional fuel cell separator 82 that employs a precious metal partial formation structure cannot stably maintain a low contact resistance.

[0030] Therefore, if we try to suppress corrosion in a severe environment where the phenomenon shown in Figure 13 is expected to occur, it will be necessary to provide Au or Pt over the entire surface of the separator substrate, which will be expensive and therefore not practical.

[0031] The fuel cell separator disclosed in Patent Document 6 uses titanium oxide as an intermediate layer when titanium is used for the separator substrate, and a non-conductive film layer when stainless steel is used for the separator substrate. A conductive film of Au or Pt is then formed on the intermediate layer by plating or sputtering, realizing a separator structure including the substrate, intermediate layer, and conductive film.

[0032] However, the intermediate titanium oxide layer and stainless steel non-conductive film do not have sufficient corrosion resistance in the severe environment required for fuel cells.

[0033] Furthermore, paragraph

[0027] of the specification of Patent Document 6 states that the conductive coating is formed of Au, Ag (silver), Cu (copper), Pt, Rh (rhodium), Ir (iridium), etc.; however, the reality is that if a metal other than Au or Pt is provided, corrosion will occur from that metal.

[0034] Conventional fuel cell separators are constructed as described above, and while they have a relatively inexpensive structure, they have the problem that they are unable to stably maintain low contact resistance with the contact objects.

[0035] The present disclosure has been made to solve the above-mentioned problems, and aims to provide a fuel cell separator and a manufacturing method thereof that have a relatively inexpensive structure and can stably reduce contact resistance with the contact object. [Means for solving the problem]

[0036] The fuel cell separator according to the present disclosure comprises a metal substrate, a conductive oxide film provided on the metal substrate, and a group of precious metal particles provided on the conductive oxide film, the group of precious metal particles including a plurality of precious metal particles, at least a portion of the plurality of precious metal particles being provided discretely, and the constituent material of each of the plurality of precious metal particles being gold or platinum. Effect of the Invention

[0037] The fuel cell separator disclosed herein has a basic separator structure that is a three-layer structure consisting of a metal substrate, a conductive oxide film, and a precious metal particle group, and therefore can stably reduce the contact resistance between the precious metal particle group with the conductive oxide film as an underlayer and the contact object.

[0038] Furthermore, the fuel cell separator of the present disclosure can be produced at relatively low cost because the amount of precious metal, such as gold or platinum, used can be reduced by providing at least a portion of the multiple precious metal particles in a discrete manner. [Brief description of the drawings]

[0039] [Figure 1] FIG. 1 is a cross-sectional view showing a basic structure of a separator which is a basic technology of the present disclosure. [Diagram 2] 1 is a cross-sectional view showing the structure of a fuel cell separator according to an embodiment of the present invention. [Diagram 3] 4 is a flowchart showing a process procedure of a manufacturing method of a fuel cell separator according to the present embodiment. [Figure 4] FIG. 2 is an explanatory diagram showing a schematic configuration of a mist CVD apparatus used in the present embodiment. [Diagram 5] FIG. 1 is an explanatory diagram showing, in table form, the degree of improvement in contact resistance according to the Au particle area ratio and the average particle size. [Figure 6] 1 is a graph showing the relationship between heating temperature and average Au particle size. [Figure 7] 1 is a graph showing the relationship between heating temperature and average area ratio of Au. [Figure 8]4 is an explanatory diagram showing, in table form, the contact resistance between the fuel cell separator of the present embodiment and a contact object in various states. FIG. [Figure 9] FIG. 9 is an explanatory diagram showing the contact resistance shown in FIG. 8 in the form of a bar graph. [Figure 10] FIG. 11 is an explanatory diagram showing, in table form, the contact resistance between a conventional fuel cell separator and a contact object in various states. [Figure 11] FIG. 11 is an explanatory diagram showing the contact resistance shown in FIG. 10 in the form of a bar graph. [Figure 12] FIG. 2 is an explanatory diagram showing an exploded view of the basic structure of a fuel cell. [Figure 13] FIG. 1 is an explanatory diagram showing problems with a conventional separator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] <Embodiment Mode> (basic structure) 1 is a cross-sectional view showing a separator basic structure 2R according to the basic technology of the present disclosure. As shown in the figure, the separator basic structure 2R includes a metal substrate 20, a conductive oxide film 21, and a precious metal particle group 22G as main components.

[0041] As shown in the figure, a conductive oxide film 21 is provided on the surface of a metal base material 20. The surface of the conductive oxide film 21 serves as a particle formation surface. On the surface of the conductive oxide film 21, a precious metal particle group 22G is provided.

[0042] The precious metal particle group 22G includes a plurality of fine particle-like precious metal particles 22, at least some of which are provided separately from one another. That is, at least some of the precious metal particles 22 have gaps between them where no precious metal particles 22 are present. The material constituting each of the precious metal particles is gold (Au) or platinum (Pt).

[0043] The precious metal particle group 22G side of the separator basic structure 2R becomes the contact surface with the contact object. That is, the precious metal particle group 22G with the conductive oxide film 21 as the base layer becomes the contact surface. The contact object may be, for example, the gas diffusion layer pair 13 and 14 present on both sides of the MEA 5 that serves as the fuel part in the fuel cell 60 shown in FIG.

[0044] In addition, a tin oxide film with improved conductivity by adding a third element such as indium or antimony is used as the conductive oxide film 21. The tin oxide film with indium added becomes an ITO (Indium Tin Oxide) film, and the tin oxide film with antimony added becomes an ATO (Antimony Tin Oxide) film. In this way, for example, an ATO film (Antimony doped tin oxide film) or an ITO film is used as the conductive oxide film 21.

[0045] (Actual structure) Fig. 2 is a cross-sectional view showing the structure of a fuel cell separator 2 according to the first embodiment of the present disclosure. An XYZ orthogonal coordinate system is depicted in Fig. 2. The fuel cell separator 2 shown in the figure is used, for example, as one of the fuel cell separators 15 and 16 used in the fuel cell 60 shown in Fig. 12.

[0046] As shown in the figure, the fuel cell separator 2 shown in FIG. 2 includes, as main components, a metal substrate 20, a pair of ATO films 21A, and a pair of precious metal particle groups 22G.

[0047] As shown in the figure, the metal base 20 has projections and recesses in the X direction and is structured to extend in the Z direction. The metal base 20 has a substantially uniform thickness. An upper ATO (antimony-doped tin oxide) film 21A is provided on the surface of the metal base 20 on the +X direction side, and a lower ATO film 21A is provided on the rear surface of the metal base 20 on the -X direction side.

[0048] In this manner, a pair of ATO films 21A are provided on both sides of the metal base 20. A structure including the metal base 20 and the pair of ATO films 21A constitutes an intermediate structure 30. In the intermediate structure 30, the upper surface of the upper ATO film 21A and the lower surface of the lower ATO film 21A each constitute particle formation surfaces.

[0049] A precious metal particle group 22G is provided on the upper surface of the upper ATO film 21A, and a precious metal particle group 22G is provided on the lower surface of the lower ATO film 21A. Hereinafter, the combination of the upper ATO film 21A and the precious metal particle group 22G provided on the upper surface of the upper ATO film 21A may be referred to as an "upper precious metal formation portion," and the combination of the lower ATO film 21A and the precious metal particle group 22G provided on the lower surface of the lower ATO film 21A may be referred to as a "lower precious metal formation portion."

[0050] Each of the pair of precious metal particle groups 22G includes a plurality of precious metal particles 22, and each of the plurality of precious metal particles is made of gold or platinum.

[0051] Therefore, a plurality of particulate (approximately spherical) precious metal particles 22 are provided on the upper surface of the upper ATO film 21A, which is the particle formation surface. At least some of the plurality of precious metal particles 22 are attached to the upper surface of the upper ATO film 21A in a discrete state. Therefore, gaps exist at least partially between the plurality of precious metal particles 22 in the upper precious metal formation portion.

[0052] Similarly, a plurality of particulate precious metal particles 22 are provided on the lower surface of the lower ATO film 21A, which is the particle formation surface. At least some of the plurality of precious metal particles 22 are attached to the lower surface of the lower ATO film 21A in a discrete state. Therefore, there are gaps at least in some of the spaces between the plurality of precious metal particles 22 in the lower precious metal formation portion.

[0053] In each of the upper and lower noble metal forming portions, the ideal state is one in which all of the multiple noble metal particles 22 are dispersed.

[0054] In this manner, a pair of precious metal particle groups 22G (a pair of a plurality of precious metal particles 22) is provided on both sides of the intermediate structural body 30 in a manner in which a plurality of precious metal particles 22 are attached.

[0055] The precious metal particle group 22G having the ATO film 21A as an underlayer in the upper precious metal forming portion or the precious metal particle group 22G having the ATO film 21A as an underlayer in the lower precious metal forming portion becomes a contact surface with the contact object.

[0056] The area ratio of the multiple precious metal particles 22 in the particle formation surface (upper surface) of the upper ATO film 21A is set to 30% or less. That is, the area ratio of the multiple precious metal particles 22 to the area of ​​the upper surface of the upper ATO film 21A is set to 30% or less.

[0057] Similarly, the area ratio of the multiple precious metal particles 22 in the particle formation surface (lower surface) of the lower ATO film 21A is set to 30% or less. That is, the area ratio of the multiple precious metal particles 22 to the area of ​​the lower surface of the lower ATO film 21A is set to 30% or less.

[0058] The average diameter (average particle size) of the plurality of precious metal particles 22 in the upper precious metal forming portion is set to 10 nm or less. Similarly, the average diameter of the plurality of precious metal particles 22 in the lower precious metal forming portion is set to 10 nm or less.

[0059] In this manner, the fuel cell separator 2 of this embodiment has the separator basic structure 2R shown in FIG. 1 on each of the front and back surfaces of the metal substrate 20.

[0060] In addition, in the fuel cell separator 2 of this embodiment, the multiple precious metal particles 22 in each of the upper precious metal formation portion and the lower precious metal formation portion are subject to an occupation area condition of {occupancy area ratio of 30% or less} and an average diameter condition of {average diameter of 10 nm or less}.

[0061] When contact with the contact object is made in the upper precious metal forming part, the plurality of precious metal particles 22 in the lower precious metal forming part do not need to satisfy the above-mentioned occupation area condition and the above-mentioned average diameter condition. Similarly, when contact with the contact object is made in the lower precious metal forming part, the plurality of precious metal particles 22 in the upper precious metal forming part do not need to satisfy the above-mentioned occupation area condition and the above-mentioned average diameter condition.

[0062] (Manufacturing method) The method for manufacturing the fuel cell separator 2 of this embodiment will be described below. Fig. 3 is a flow chart showing the procedure of the method for manufacturing the fuel cell separator 2. The method for manufacturing the fuel cell separator 2 will be described below with reference to this figure.

[0063] First, in step S1, an intermediate structure 30 (see FIG. 2) is prepared, which includes a metal base 20 and a pair of ATO films 21A provided on the front and back surfaces of the metal base 20. That is, the intermediate structure 30 is an intermediate structure before a pair of precious metal particle groups 22G is formed. Note that the metal base 20 may be a SUS304 base material or a Ti base material, which will be described later.

[0064] The intermediate structure 30 is manufactured by an existing method. For example, a pair of ATO films 21A may be formed on both sides of the metal base 20 by using a mist CVD method. Specifically, ultrasonic waves are applied to a raw material solution using SnCl2 (tin chloride) as a raw material to generate raw material mist, and the raw material mist is sprayed onto the front and back surfaces of the heated metal base 20, thereby forming the ATO films 21A on both sides of the metal base 20.

[0065] 4 is an explanatory diagram showing a schematic configuration of the mist CVD apparatus 7 used in this embodiment to form the fuel cell separator 2. The XYZ orthogonal coordinate system is shown in the figure. Steps S2 and S3 described below are performed using the mist CVD apparatus 7 shown in FIG.

[0066] The mist CVD apparatus 7 includes a heating chamber 40, a particle formation chamber 50, a transport path 45, and a transport path 46 as main components.

[0067] The heating chamber 40 has a pair of lamp mounting stands 41 on one side (the side on the -X side in the figure) and the other side (the side on the +X side in the figure) inside, and each of the pair of lamp mounting stands 41 mounts a plurality of infrared lamps 42. The pair of the plurality of infrared lamps 42 is disposed so that the infrared radiation directions face each other along the X direction, and therefore the space within the heating chamber 40 sandwiched between the pair of lamp mounting stands 41 becomes a heating space 40s.

[0068] Therefore, the heating space 40s in the heating chamber 40 can be heated by the infrared radiation emitted by the multiple infrared lamps 42 provided on each of the pair of lamp mounting tables 41.

[0069] A transport path 45 is provided at the upper opening of the heating chamber 40, a transport path 46 is provided at the lower opening of the transport path 45, and a particle formation chamber 50 is provided below the heating chamber 40 via the transport path 46.

[0070] A plurality of ultrasonic vibrators 38 (two ultrasonic vibrators 38 in FIG. 4) are provided on the bottom surface of the particle formation chamber 50, and the raw material solution 36 is accommodated below. The raw material solution 36 is a solution containing a precious metal such as gold or platinum. In the particle formation chamber 50, the space above the raw material solution 36 becomes a mist space 50s.

[0071] By performing ultrasonic vibration processing using the multiple ultrasonic vibrators 38, ultrasonic waves are applied to the raw material solution 36 in the particle formation chamber 50, atomizing the raw material solution 36 and generating raw material mist MT. The generated raw material mist MT accumulates in the mist space 50s. For example, the raw material mist MT can be reliably accumulated in the mist space 50s by closing the opening at the top of the particle formation chamber 50 or the transport path 46 except when the intermediate structure 30 is being transported into the particle formation chamber 50. Note that an air curtain, for example, can be used as a method for closing the space.

[0072] The intermediate structure 30 is held in a suspended state by a holding member 43 connected via a connection ring 43r. The holding member 43 is capable of moving up and down along the ±Z directions.

[0073] 3 is performed using the mist CVD apparatus 7 having such a configuration. In step S2, the holding member 43 is lowered from above the heating chamber 40 along the transport direction D2 going downward, and the intermediate structure 30 is placed in the heating space 40s of the heating chamber 40 via the transport path 45, thereby heating the intermediate structure 30. Therefore, the upper and back surfaces of the intermediate structure 30, i.e., the upper surface of the upper ATO film 21A and the lower surface of the lower ATO film 21A, are heated by the multiple infrared lamps 42, respectively.

[0074] In step S3, the intermediate structure 30 after the heat treatment in step S2 is further lowered by the holding member 43 along the conveying direction D2, and the intermediate structure 30 is placed in the mist space 50s containing the raw material mist MT via the conveying path 46.

[0075] The upper surface of the upper ATO film 21A and the lower surface of the lower ATO film 21A are immediately after the heat treatment in step S2. Therefore, when the raw material solution 36 contains gold (Au), the chemical reaction {2AuCl3→2Au+3Cl2} in the mist CVD method can be caused.

[0076] Then, in the mist space 50s, the raw material mist MT containing Au atoms that has been converted into mist by the above-mentioned chemical reaction comes into contact with the upper surface of the upper ATO film 21A and the lower surface of the lower ATO film 21A. As a result, a plurality of Au particles adhere to the upper surface of the upper ATO film 21A and the lower surface of the lower ATO film 21A as a plurality of precious metal particles 22.

[0077] In this manner, the precious metal particle group 22G is formed on the upper surface of the upper ATO film 21A and on the lower surface of the lower ATO film 21A. The precious metal particle group 22G includes a plurality of precious metal particles 22 attached to the particle formation surface of the ATO film 21A. Each of the plurality of precious metal particles 22 has a particulate shape, and at least a portion of the plurality of precious metal particles 22 is provided in a discrete manner.

[0078] The mist contact time, which is the execution time of step S3, is set to a sufficiently short time of less than 1 second so that the area occupied by the multiple precious metal particles 22 within the particle formation surface of each of the pair of ATO films 21A is 30% or less and the average diameter of the multiple precious metal particles 22 is 10 nm or less.

[0079] In this manner, steps S1 to S3 can be carried out to manufacture a fuel cell separator 2 having the structure shown in Fig. 2. This fuel cell separator 2 satisfies the above-mentioned occupied area condition and average diameter condition.

[0080] The particle diameter of each of the multiple precious metal particles 22 and the area ratio of the particles within the particle formation surface can be adjusted by the heating temperature of the intermediate structure 30 in the heat treatment in step S2 and the mist contact time, which is the execution time of step S3.

[0081] Furthermore, by making the concentration of the raw material solution 36 relatively low and making the mist contact time relatively short, all of the multiple precious metal particles 22 can be attached to the particle formation surface of the ATO film 21A in a discrete state.

[0082] Furthermore, if it is determined that the occupied area ratio and the average diameter are insufficient in a single execution of steps S2 and S3, the processes of steps S2 and S3 may be repeated multiple times. Specifically, after the first execution of step S3, the holding member 43 is raised in the +Z direction, the incomplete fuel cell separator 2 is placed again in the heating chamber 40, and step S2 is executed a second time, and after execution of step S2, step S3 is executed again, thereby executing S2 and S3 a second time.

[0083] Similarly, steps S2 and S3 may be executed a third time or later. In this manner, the intermediate structure 30 or the unfinished fuel cell separator 2 may be placed in the heating chamber 40 or the particle formation chamber 50 a plurality of times, and steps S2 and S3 may be executed a plurality of times.

[0084] (Experimental Results) 5 is an explanatory diagram showing, in a table format, the degree of improvement in contact resistance according to the average Au area ratio and the average particle size. Note that "average Au area ratio (%)" refers to the ratio (%) of the area occupied by Au particles, which are the precious metal particles 22, to the area of ​​the particle-formed surface. For example, when the entire upper surface of the upper ATO film 21A becomes the particle-formed surface, the area of ​​the entire upper surface of the upper ATO film 21A becomes the "area of ​​the particle-formed surface."

[0085] The term "average particle size (nm)" refers to the average diameter (nm) of the multiple noble metal particles 22 provided on the particle formation surface. 2 ) is the degree of resistance reduction (mΩcm) before and after the formation of Au particles 2 2. Specifically, the structure before the Au particles are formed is the intermediate structure 30 shown in FIG. 2, and the structure after the Au particles are formed is the fuel cell separator 2 shown in FIG. 2, in which Au particles are formed as precious metal particles 22.

[0086] As shown in the figure, by adjusting the mist contact time, which is the execution time of step S3, etc., the Au average area ratio is set to "30%" and the average particle size is set to "5.8 nm" in condition 1, the Au average area ratio is set to "22%" and the average particle size is set to "9.3 nm" in condition 2, and the Au average area ratio is set to "93%" and the average particle size is set to "24.7 nm" in condition 3.

[0087] As shown in Figure 5, under condition 1, the degree of improvement in contact resistance was 6 (mΩcm 2 ) In other words, in condition 1, 2Similarly, the contact resistance improvement in condition 2 was 5.7 (mΩcm 2 ), and the degree of improvement in contact resistance for condition 3 is 4 (mΩcm 2 )

[0088] From the experimental results shown in Figure 5, conditions 1 and 2 have a significantly smaller average Au area ratio than condition 3. In other words, conditions 1 and 2 have a smaller amount of Au particle adhesion to the particle formation surface than condition 3, but the degree of improvement in contact resistance is greater than that of condition 3. Therefore, if emphasis is placed on achieving a relatively large degree of improvement in contact resistance with the minimum necessary amount of Au particles, it is estimated that the optimal conditions are an average Au area ratio of 30% or less and an average particle size of 10 nm.

[0089] 6 is a graph showing the relationship between heating temperature and average Au particle size. In the figure, the horizontal axis is heating temperature (°C) and the vertical axis is Au average particle size (nm). Note that the heating temperature indicates the temperature (°C) in the heating space 40s when the heating process of step S2 is performed, and the Au average particle size indicates the average diameter (nm) of a plurality of precious metal particles 22 when the precious metal particles 22 are Au particles.

[0090] In the same figure, particle size change L1 shows the change when the mist contact time, which is the execution time of step S2, is set to 0.1 (sec), and particle size change L2 shows the change when the mist contact time is set to 0.5 (sec).

[0091] As shown in particle size change L2 in the figure, when the mist contact time is 0.5 seconds, the average Au particle size exceeds 10 nm when the heating temperature exceeds 430°C. On the other hand, as shown in particle size change L1, when the mist contact time is 0.1 seconds, the average Au particle size is kept below 7 nm in the heating temperature range of 350 to 450°C.

[0092] 7 is a graph showing the relationship between heating temperature and the average area ratio of Au. In this figure, the horizontal axis is heating temperature (°C) and the vertical axis is the average area ratio of Au (%). Note that the average area ratio of Au indicates the ratio (%) of the formation area of ​​a plurality of precious metal particles 22 to the area of ​​the particle formation surface when the precious metal particles 22 are Au particles.

[0093] In the figure, area ratio change L3 indicates the change when the mist contact time is set to 0.1 (sec), and area ratio change L4 indicates the change when the mist contact time is set to 0.5 (sec).

[0094] As shown in area ratio change L4 in the figure, when the mist contact time is 0.5 seconds, the average Au area ratio exceeds 30% when the heating temperature is below 400°C. On the other hand, as shown in area ratio change L3, when the mist contact time is 0.1 seconds, the average Au area ratio is kept below 30% in the heating temperature range of 350 to 450°C.

[0095] Therefore, from the experimental results shown in Figures 6 and 7, it can be inferred that when the heating temperature range in step S2 is {350 to 450°C}, in order to keep the average Au area ratio at 30% or less and the average Au particle size at 10 nm or less within the heating temperature range, the mist contact time needs to be set to 0.1 seconds or less.

[0096] Fig. 8 is an explanatory diagram showing, in the form of a table, the contact resistance with a contact object in various states of the fuel cell separator 2 according to the embodiment. Fig. 9 is an explanatory diagram showing, in the form of a bar graph, the contact resistance shown in Fig. 8. Specifically, the contact object may be the pair of gas diffusion layers 13 and 14 in the fuel cell 60 shown in Fig. 12. Note that the unit of the resistance values ​​shown in Figs. 8 and 9 is all mΩcm. 2 It is.

[0097] The experimental results shown in Figures 8 and 9 were obtained by setting the operating specifications of the mist CVD apparatus 7 shown in Figure 4 as follows: The operating specifications are: the number of ultrasonic transducers 38 is "2", the ultrasonic frequency of each ultrasonic transducer 38 is "1.6 MHZ", and the concentration of the AuCl3 solution serving as the raw material solution 36 is "0.003 mol / L".

[0098] 8 and 9, the SUS304 substrate and the Ti substrate each show a specific structure of the metal substrate 20. The SUS304 substrate is a typical metal substrate on which a non-conductive film has been formed in advance, and the Ti substrate is a typical metal substrate on which a TiO x The titanium oxide film is formed in advance.

[0099] 8 and 9, "before deposition" shows the structure before the precious metal particle groups 22G are formed. "after deposition" shows the structure after the precious metal particle groups 22G are formed. In other words, "after deposition" shows the overall structure of the fuel cell separator 2.

[0100] In the column "Before deposition", "Metal substrate only" shows only the structure of the metal substrate 20 before the conductive oxide film 21 (ATO film 21A) is formed. Furthermore, in the column "Before deposition", "After ATO film formation" shows the structure of the intermediate structure 30 including the metal substrate 20 and the ATO film 21A. The ATO film 21A can be formed on the metal substrate 20 by using an existing mist CVD method in which ultrasonic waves are applied to a raw material solution 36 using SnCl2 as a raw material to obtain a raw material mist MT.

[0101] The fuel cell separator 2 after deposition will be described in detail below. Ultrasonic waves are applied from an ultrasonic vibrator 38 to a raw material solution 36 made from AuCl3, atomizing (turning the raw material solution 36 into mist) to obtain raw material mist MT. Thereafter, by disposing the intermediate structure 30 in a state in which the raw material mist MT is retained in the mist space 50s, a precious metal particle group 22G can be formed on the particle formation surface of the ATO film 21A (step S3 in FIG. 3).

[0102] That is, a pair of precious metal particle groups 22G can be formed on the upper surface of the upper ATO film 21A and on the lower surface of the lower ATO film 21A by using the mist CVD method using the mist CVD apparatus 7. The multiple precious metal particles 22 contained in each of the pair of precious metal particle groups 22G become multiple Au particles. In this manner, by using the mist CVD method using the mist CVD apparatus 7 for the intermediate structure 30, the fuel cell separator 2 shown in FIG. 2 can be completed.

[0103] At this time, the average area ratio of Au in the fuel cell separator 2 was 30%, and the average Au particle size was 5.8 nm.

[0104] In Figures 8 and 9, "Before durability test" in the "After deposition" column indicates the state before the fuel cell separator 2 was used, and "After durability test" indicates the state after the fuel cell separator 2 was used in the corrosive and oxidative environment expected for a fuel cell.

[0105] As a durability test, a corrosion oxidation test was conducted in which the fuel cell separator 2 was held for three days in a solution of 800 ml of sulfuric acid (pH 3) containing 3 ppm hydrofluoric acid and held at 80° C. while a current of 0.9 V was applied thereto.

[0106] 8 and 9, when the metal substrate 20 is a SUS304 substrate, the contact resistance is "76" for the metal substrate 20 alone, improves to "8.9" for the intermediate structure 30, and improves to "2.9" for the fuel cell separator 2. Furthermore, even after the durability test, the contact resistance of the fuel cell separator 2 is maintained at a low resistance value of "3.2."

[0107] 8 and 9, when the metal substrate 20 is a Ti substrate, the contact resistance is "6.2" for the metal substrate 20 alone, "8.4" for the intermediate structure 30, and improves to "2.1" for the fuel cell separator 2. Furthermore, even after the durability test, the contact resistance of the fuel cell separator 2 is maintained at a relatively low resistance value of "3.8."

[0108] As shown in FIG. 9, the fuel cell separator 2 of this embodiment has a target reference resistance value SR (5 mΩcm) after being used in a severe corrosive and oxidative environment expected in a fuel cell. 2 ) and maintains a low contact resistance below that of the conventional method.

[0109] That is, it is understood that the low contact resistance of the fuel cell separator 2 of this embodiment can be stably maintained for a long period of time.

[0110] Fig. 10 is an explanatory diagram showing, in table form, the contact resistance between a comparative fuel cell separator and a contact object in various states. Fig. 11 is an explanatory diagram showing, in bar graph form, the contact resistance shown in Fig. 10. Note that the unit of resistance values ​​shown in Fig. 10 and Fig. 11 is all mΩcm. 2 It is.

[0111] 8 and 9, the experimental results shown in FIGS. 10 and 11 were obtained under the operating specifications of the mist CVD apparatus 7 described above.

[0112] The comparative fuel cell separator has a structure in which a precious metal particle group 22G (a plurality of precious metal particles 22) is provided directly on a metal substrate 20.

[0113] In Figures 10 and 11, the SUS304 substrate and the Ti substrate each show the specific structure of the metal substrate 20. "Before deposition" shown in Figures 10 and 11 shows the structure before the precious metal particle groups 22G are formed. "After deposition" shows the structure after the precious metal particle groups 22G are formed. In other words, "after deposition" shows the overall structure of the comparative fuel cell separator.

[0114] Using the mist CVD apparatus 7 shown in FIG. 4, the intermediate structure 30 is replaced with only the metal base material 20, and steps S1 to S3 shown in FIG. 3 are performed to form a precious metal particle group 22G on the particle formation surface of the metal base material 20.

[0115] In the column "Before deposition", "Metal substrate only" indicates the structure of only the metal substrate 20 before the formation of the precious metal particle groups 22G.

[0116] In the "After deposition" column, "Before durability test" indicates the state before the comparative fuel cell separator was used, and "After durability test" indicates the state after the comparative fuel cell separator was used in the corrosive and oxidative environment expected for a fuel cell.

[0117] As a durability test, a corrosion test was conducted in which the comparative fuel cell separator was kept for three days in a solution of 800 ml of sulfuric acid (pH 3) containing 3 ppm hydrofluoric acid and kept at 80°C while a current of 0.9 V was applied to it, similar to the experimental results shown in Figures 8 and 9.

[0118] 10 and 11, when the metal substrate 20 was a SUS304 substrate, the contact resistance of the metal substrate 20 alone was "73", and immediately after the completion of the comparative fuel cell separator, this improved to "1.73". However, after the durability test, the contact resistance of the comparative fuel cell separator significantly deteriorated, with the resistance value increasing to "21".

[0119] 10 and 11, when the metal substrate 20 was a Ti substrate, the contact resistance was 6.4 for the metal substrate 20 alone, and improved to 2.25 immediately after the completion of the comparative fuel cell separator. However, after the durability test, the contact resistance of the comparative fuel cell separator significantly deteriorated, and the resistance value rose to 92.7.

[0120] As shown in FIG. 11, the comparative fuel cell separator had a target standard resistance value SR (5 mΩ cm) after being used in an assumed severe corrosive and oxidative environment. 2 ) resulting in a high contact resistance value that far exceeds the

[0121] Thus, from the experimental results shown in Figures 10 and 11, it was found that in a comparative fuel cell separator having precious metal particle groups 22G on both sides of the metal substrate 20, even if the contact resistance was reduced immediately after completion, the resistance value of the contact resistance would increase significantly when used in an environment expected for a fuel cell, and the low contact resistance could not be maintained.

[0122] That is, from the comparison results of Figures 8 and 9 with Figures 10 and 11, it was found that in order to maintain a low contact resistance of the fuel cell separator even after it is used in a severe environment assumed for a fuel cell, it is important to provide the conductive oxide film 21 (ATO film 21A) as an underlayer of the precious metal particle group 22G. That is, it was found that the inclusion of the conductive oxide film 21 having high corrosion resistance properties is an essential condition for the separator basic structure 2R.

[0123] The experimental results shown in Figures 8 to 11 prove that the fuel cell separator 2 of this embodiment having the separator basic structure 2R can stably maintain low contact resistance over a long period of time.

[0124] (effect) The fuel cell separator 2 of this embodiment has a separator basic structure 2R (see Figure 1) which is a three-layer structure of a metal substrate 20, a conductive oxide film 21, and precious metal particles 22, and therefore can stably reduce the contact resistance between the precious metal particle group 22G and the contact object.

[0125] This effect is also evident from the experimental results shown in Figures 8 to 11. The above-mentioned contact objects are fuel cell components, specifically, gas diffusion layer pairs 13 and 14 present on both sides of MEA 5, which serves as the power generation section, shown in Figure 12.

[0126] In addition, the fuel cell separator 2 of this embodiment can be produced at relatively low cost by providing at least some of the plurality of precious metal particles 22 in a discrete manner, thereby reducing the amount of precious metal, such as gold or platinum, used.

[0127] Furthermore, the resistance value of the contact resistance can be stabilized by using the ATO film 21A as the conductive oxide film 21 that serves as the underlayer for the precious metal particle group 22G in the fuel cell separator 2. This effect is also evident from the experimental results shown in FIGS.

[0128] Additionally, in the fuel cell separator 2 of this embodiment, the average diameter of the multiple precious metal particles 22 is set to 10 nm or less, which allows the contact area with the pair of gas diffusion layers 13 and 14 to be relatively large, since the gas diffusion layer (GDL) is fibrous and porous.

[0129] Therefore, in the fuel cell separator 2 of this embodiment, by setting the average diameter of the plurality of precious metal particles 22 to 10 nm or less, the contact resistance with the contact object can be further reduced.

[0130] In addition, by performing an experiment as shown in FIG. 5 under conditions where a large number of Au average particle sizes below 10 nm are set, the lower limit of the Au average particle size can be identified in advance as a significant value exceeding "0." For example, the minimum value of the Au average particle size that satisfies the standard resistance value SR or less can be set as the lower limit. Therefore, it is desirable to set the Au average particle size between the previously identified lower limit and the upper limit of 10 nm.

[0131] Additionally, in the fuel cell separator 2 of this embodiment, the area ratio of the multiple precious metal particles 22 within the particle formation surface of the conductive oxide film 21 (ATO film 21A) is set to 30% or less.

[0132] Therefore, the fuel cell separator 2 of this embodiment can reduce the contact resistance with the contact object while keeping the amount of Au or Pt used as the precious metal particles 22 to a minimum necessary.

[0133] In addition, by performing an experiment as shown in FIG. 5 under conditions where a large number of Au average area ratios below 30% are set, the lower limit of the Au average area ratio can be recognized in advance as a significant value exceeding "0." For example, the minimum value of the Au average area ratio that is equal to or less than the reference resistance value SR can be set as the lower limit. Therefore, it is desirable to set the Au average area ratio between the previously recognized lower limit and the upper limit of 30%.

[0134] In the manufacturing method of the fuel cell separator of this embodiment shown in Figure 3, by performing step S3, it is possible to obtain the fuel cell separator 2 of this embodiment, which includes a separator basic structure 2R consisting of a metal substrate 20, a conductive oxide film 21, and precious metal particles 22.

[0135] The fuel cell separator 2 including the separator basic structure 2R can stably achieve low contact resistance between the precious metal particle group 22G and the contact object.

[0136] In addition, by changing the mist contact time, which is the execution time of step S3, it is possible to adjust the average diameter of the multiple precious metal particles 22 contained in the precious metal particle group 22G and the occupied area ratio of the multiple precious metal particles on the particle formation surface.

[0137] In the manufacturing method of this embodiment, the mist contact time is set so that the area occupied by the multiple precious metal particles 22 is 30% or less, and therefore the amount of precious metal (Au, Pt) used as the precious metal particles 22 is kept to a minimum necessary, thereby making it possible to obtain a fuel cell separator 2 having reduced contact resistance with the contact object.

[0138] In addition, in the present disclosure, the embodiments can be modified or omitted as appropriate within the scope of the disclosure. [Explanation of symbols]

[0139] 2. Fuel cell separator 2R Separator Basic Structure 7. Mist CVD Equipment 20 Metal substrate 21 Conductive oxide film 21A ATO film 22 Noble metal particles 22G Noble metal particle group 36 Raw material solution 38 Ultrasonic vibrator 40 Heating chamber 50 Particle formation chamber

Claims

1. A metal substrate; A conductive oxide film provided directly on the surface of the metal substrate; a group of precious metal particles provided on the conductive oxide film; The precious metal particle group includes a plurality of precious metal particles, At least a portion of the plurality of precious metal particles is provided discretely, The constituent material of each of the plurality of precious metal particles is gold or platinum; the average diameter of the plurality of precious metal particles is 10 nm or less; the noble metal particle group is formed on a particle formation surface of the conductive oxide film, the area ratio of the plurality of precious metal particles to the grain formation surface is 30% or less; Fuel cell separator.

2. 2. The fuel cell separator according to claim 1, The conductive oxide film is an antimony-doped tin oxide film. Fuel cell separator.

3. A method for manufacturing a fuel cell separator, comprising the steps of: (a) providing an intermediate structure including a metal substrate and a conductive oxide film disposed directly on a surface of the metal substrate; (b) heating the intermediate structure in a heating chamber; (c) placing the intermediate structure after the step (b) is performed in a mist space containing raw material mist; The mist space is provided in a particle formation chamber separate from the heating chamber, The raw material mist is obtained by atomizing a raw material solution containing a precious metal such as gold or platinum, After the step (c) is performed, a precious metal particle group including a plurality of precious metal particles is formed on the particle formation surface of the conductive oxide film, The mist contact time, which is the execution time of the step (c), is set so that the occupation area ratio of the plurality of precious metal particles in the particle formation surface is 30% or less and the average diameter of the plurality of precious metal particles is 10 nm or less. A method for manufacturing a fuel cell separator.

Citation Information

Patent Citations

  • Anti-reverse composite coating for fuel cell bipolar plate

    CN111525151A

  • Metal plate for fuel cell, separator for fuel cell using same, and polymer electrolyte fuel cell using the separator for fuel cell

    JP2005293877A

  • Fuel cell separator and its manufacturing method

    JP2009238438A

  • Corrosion resistant film for fuel cell separator, and fuel cell separator

    JP2010182593A

  • Base material for metal separator, method of manufacturing the same, and metal separator

    JP2011029008A